2022
DOI: 10.1108/hff-01-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation at the welded interface of an elastic solid and unsaturated poro-thermoelastic solid

Abstract: Purpose The purpose of this paper is to investigate propagation characteristics of seismic waves at the welded interface of an elastic solid and unsaturated poro-thermoelastic solid. Design/methodology/approach A theoretical formulation of partially saturated poro-thermoelastic solid is used in this study established by Zhou et al. (2019). The incidence of two primary waves (P and SV) is taken. The incident wave from the elastic solid induces two reflected waves and five refracted waves. Due to viscous pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recently, Kumar et al (2021) investigated the propagation characteristics (attenuation, velocity, loci of vertical slowness, phase shift, energy) of plane harmonic waves on the stress-free surface of a partially saturated poro-thermoelastic media. Later, Kumar et al (2022) examined the partition of incident energy among distinct reflected and refracted waves at the welded interface of an elastic solid and unsaturated poro-thermoelastic solid.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kumar et al (2021) investigated the propagation characteristics (attenuation, velocity, loci of vertical slowness, phase shift, energy) of plane harmonic waves on the stress-free surface of a partially saturated poro-thermoelastic media. Later, Kumar et al (2022) examined the partition of incident energy among distinct reflected and refracted waves at the welded interface of an elastic solid and unsaturated poro-thermoelastic solid.…”
Section: Introductionmentioning
confidence: 99%
“…On a magneto-thermoelastic material with void pores, Alharbi et al (2021) evaluated the effects of gravity and memory-dependent derivatives. Kumar et al (2022) reported a discussion on the propagation of waves at the interface of an elastic solid and an unsaturated poro-thermoelastic solid.…”
Section: Introductionmentioning
confidence: 99%